Hide and seek in the Bay of Biscay—a functional investigation of marine megafauna and small pelagic fish interactions. (16th October 2018) - Lambert, Charlotte; Authier, Matthieu; Doray, Mathieu; Dorémus, Ghislain; Spitz, Jérome; Ridoux, Vincent; ,
Abstract: Prey and predator distributions influence one another. Understanding the scale and the orientation of predator–prey spatial correlations is crucial in foraging ecology. Growing evidence suggests that predator–prey interactions are more constrained by functional characteristics of both the predator and the prey. Unfortunately, in marine pelagic systems, the scale and orientation of spatial correlations between predators and prey have been only little explored from a functional point of view. We tested the existence of fine-scale association between predators and fish functional groups. Visual predator sightings and acoustic fish records were collected synchronously during oceanographic surveys from 2004 to 2014. Prey biomass was integrated by nautical miles and split into four size classes (<10 cm; 10–20 cm; 20–30 cm; >30 cm) and two depth layers (surface, deep). We computed the relative biomass by prey size and depth category from 0 to 12 nm around predator sightings to determine the predators' proximity to local prey biomass. Two cetaceans (common, bottlenose dolphins) and three seabirds (northern gannets, auks, northern fulmars) were studied. No association was found in fulmars, indicating they probably do not feed on considered fishes in the area. Gannets and auks were positively correlated with local prey biomass for sizes <20 cm at both depth layers. Significant negative relationships were found between common dolphins and prey size classes <20 cm at both depth layers, and between bottlenose dolphins and all size ranges at the deeper layer. Our results suggest that the fine-scale spatial overlap of predator and prey is influenced by their functional traits, and that prey exhibit predator avoidance behaviour in presence of swimming predators but not of flying ones.